2021
DOI: 10.1152/ajpgi.00431.2020
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA enables AIM2 inflammasome activation and hepatocyte pyroptosis in nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is typified by accumulating excess liver triacylglycerol, inflammation, and liver dysfunction. This study was aimed to investigate the role of mitochondrial DNA synthesis-induced activation of Absent in melanoma 2 (AIM2) inflammasome and pyroptosis in NAFLD. Mice were raised on a high-fat diet for 24 weeks to establish NAFLD models. F4/80 immunofluorescence was performed to reflect the inflammatory response in the liver of mice. Western blot, ELISA, and immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 32 publications
0
31
1
Order By: Relevance
“…At present, several laboratory studies have examined the implication of AIM2 in the development of steatosis and NASH in mice, while human studies are still lacking [ 122 ]. AIM2 inflammasome has been found to be overexpressed and activated in the liver of the HFD-induced NAFLD mouse model [ 43 , 44 ]. Overexpress of the AIM2 gene in mice aggravated HFD-induced NAFLD and stimulated inflammatory cell infiltration and increased expression of inflammation-related genes (IL-1β and IL-18) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, several laboratory studies have examined the implication of AIM2 in the development of steatosis and NASH in mice, while human studies are still lacking [ 122 ]. AIM2 inflammasome has been found to be overexpressed and activated in the liver of the HFD-induced NAFLD mouse model [ 43 , 44 ]. Overexpress of the AIM2 gene in mice aggravated HFD-induced NAFLD and stimulated inflammatory cell infiltration and increased expression of inflammation-related genes (IL-1β and IL-18) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the AIM2 inflammasome and its physiological relevance to NAFLD are poorly understood. At present, several studies have reported that AIM2 inflammasome activation may contribute to the progression of steatosis to NASH [ [42] , [43] , [44] ]. However, the specific role of AIM2 inflammasome in steatosis and whether it can be regulated by NAG-1/GDF15 has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…39 Mitochondrial damage and mtDNA release modulate the activation of absent in melanoma 2 and NLRP3 inflammasomes, leading to the maturation and secretion of IL-1β and IL-18, which trigger pyroptosis that exacerbates liver inflammation and NAFLD progression. 40 The activity of many inflammasomes involved in NAFLD-NASH progression has been described, and the main difference lies in the ligand recognition sites and the adapter molecules. 41 Pyroptosis-inducing activity is carried out through GSDMD, and its overexpression is related to the spontaneous induction of liver damage without a secondary factor, which indicates that it is a crucial mechanism involved in NAFLD pathogenesis.…”
Section: Hepatic Inflammasome and Pyroptosismentioning
confidence: 99%
“…It was observed that this extracellular mtDNA is the driver for the activation of macrophages, and the subsequent induction of the cytokine IL-1β, contributing to the establishment of chronic inflammation [ 97 ]. AIM2 has also been observed to sense mtDNA from events of mitochondrial stress, such as increased cell levels of cholesterol, which lead to the extravasation of mtDNA [ 98 ], and in non-alcoholic fatty liver disease, driving inflammation and hepatocyte pyroptosis [ 99 ].…”
Section: The Mtdna Receptors and Their Role In Inflammatory Processes - Do They Constitute A Possible Link With Sars-cov-2?mentioning
confidence: 99%